2021
DOI: 10.3389/fpsyg.2020.576610
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Growth Dimensions Differently Mediate the Relationship Between National Identity and Interpersonal Trust Among Young Adults: A Study on COVID-19 Crisis in Italy

Abstract: BackgroundIn Italy, the COVID-19 pandemic has caused a collective trauma. Post-traumatic growth (PTG) has been defined as the subjective experience of positive psychological changes as a result of a traumatic event. PTG can involve changes in five psychological main dimensions: relating to others, new possibilities, personal strength, spiritual change, and appreciation of life. In the context of national emergencies, those PTG dimensions encompassing changes at the social level (e.g., relating to others) can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 64 publications
1
19
0
2
Order By: Relevance
“…Previous studies have reported positive associations between openness to experience, emotional expression, and posttraumatic growth (e.g., Jaarsma et al, 2006 ). It is possible that e-motions lead to posttraumatic growth by fostering positive core beliefs (e.g., openness to the future and identification with humanity; Vasquez et al, 2021 ; Ellena et al, 2020 ) and emotional strengths (e.g. bravery, humor and social intelligence, Casali et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported positive associations between openness to experience, emotional expression, and posttraumatic growth (e.g., Jaarsma et al, 2006 ). It is possible that e-motions lead to posttraumatic growth by fostering positive core beliefs (e.g., openness to the future and identification with humanity; Vasquez et al, 2021 ; Ellena et al, 2020 ) and emotional strengths (e.g. bravery, humor and social intelligence, Casali et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In exceptional circumstances, such as natural disasters (e.g., hurricanes and earthquakes), traumas are experienced by entire communities bringing out collective traumatic dynamics (Lowe et al, 2013 ; Manove et al, 2019 ; Wlodarczyk et al, 2016 ). Taking into account the health and social impact of COVID-19 among the Italian population, the ongoing COVID-19 pandemic presents characteristics of collective trauma experiences that have stimulated national identity and interpersonal trust (Ellena et al, 2020 ). Collective traumas have been found to elicit intense sharing of emotions (offline and online) among members of concerned communities (Rimé et al, 2020 ).…”
Section: Sharing Emotions Onlinementioning
confidence: 99%
“…Contrary to what we expected, we did not find a significant effect of the weeks of lockdown on the levels of post-traumatic growth, except for the dimension of “searching new possibilities.” This finding is particularly striking if we consider that the levels of stress and of psychiatric symptoms tended to increase over time [ 54 ]; it may be that PTG is not related to the duration of the traumatic event, but it is related to the nature of the trauma and to the personality traits and characteristics of the individual [ 108 ]. Of course, this interpretation deserves more studies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the cross-sectional design of the survey prevents us to delineate any causal relationship between the selected variables. Finally, several variables, such as social cohesion, national identity and interpersonal trust, personality traits and cognitive styles should have had an impact on the levels of post-traumatic growth [ 108 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study had a different methodology and considered PTG as a dichotomous concept, with the score of 57 as indicative of the presence of growth. Ellena et al (2020) similarly reported higher levels of growth in all dimensions in young adults from Italy [37]. Specifically, their sample reported moderate growth levels in all dimensions except spiritual change.…”
Section: Discussionmentioning
confidence: 89%